Unusual mortalities of the eastern black rhinoceros (Diceros bicornis michaeli) due to clostridial enterotoxaemia in Ol Jogi Pyramid Sanctuary, Kenya - David Ndeereh; Benson Okita-Ouma; Jamie Gaymer; Mathew Mutinda; Francis Gakuya (Pachyderm)
Nine eastern black rhinoceroses (Diceros bicornis michaeli) developed clinical clostridial enterotoxaemia between May and July 2010 in the Pyramid Black Rhino Sanctuary within the Ol Jogi Conservancy, Laikipia, Kenya. The rhinos presented with a per-acute syndrome characterized by severe abdominal pain manifested by struggling and rolling on the ground and laboured breathing, and they died within three hours after being sighted sick. Necropsy and histopathology revealed severe pathology in the gastro-intestinal tract. Grossly, the small and large intestines were congested and oedematous. All the rhinos had variable amounts of haemorrhagic fluid in the intestines. Microscopically, the most characteristic lesion was severe necrotizing haemorrhagic enteritis. Numerous Gram-positive rod-shaped bacterial colonies that were identified to be Clostridium spp. were occasionally seen in the intestinal mucosa. Clostridium perfringens type A was isolated from the stomach contents. C. perfringens was postulated as the aetiological agent with the infection triggered probably by change of habitat following a prolonged period of drought that was followed by above-normal rainfall.